Estimated Reduction in Solids During Sheep Bedding Composting as a Function of the Composition of the Organic Fractions - Orrico Junior, Marco Antonio Previdelli; Orrico, Ana Carolina Amorim; Manarelli, Débora Maurício; Lopes, Walter Renato Teixeira; Schwingel, Alice Watte [UNESP] (Taylor & Francis, 2018)
The different organic matter fractions of residues significantly impact the degradability of organic material in composting windrows. Based on that, this study aimed to find out the organic matter fractions that most impact the breakdown rate during composting, besides proposing models to estimate the solids reductions in sheep bedding composting windrows. To that end, 24 sheep beddings from different locations and varied composition were composted so as to ensure the representativeness of the sample. The models found for reduction in total (TS) and volatile (VS) solids as a function of compostable organic matter (COM) and organic matter resistant to composting (OMRC) were not significant. Lignin had correlation coefficients of −0.6, −0.89, and −0.84 in relation to temperature, TS reduction, and VS reduction, respectively. The hemicellulose:lignin ratio was the parameter most correlated with temperature (0.69), TS reduction (0.91), VS reduction (0.92), and nitrogen (0.5), which led to more significant predictive models. It can be concluded that the hemicellulose:lignin ratio is the parameter that most impacts the breakdown of organic matter and nitrogen losses in sheep bedding composting windrows.